Kontribusi Program Hutan Kemasyarakatan Terhadap Pendapatan Masyarakat - Theresia Nadya Randa Ma; Ludji Michael Riwu Kaho; Astin E. Mau (Wana Lestari, 2023)
Community forest designed to reduce the poverty caused by the increasing population. The increasing population will our condition to the other problems, more complex. Poverty are not only scattered in urbanareas but also in rural areas including around the forests. One of the potential solution for local community around the forests is Community Forest (HKm) program. Community Forest (HKm) is astate forest whose main use is intended to empower local communities. The existence of HKm is expected to improve the welfare of the community, especially those living around forest areas. This study aims to determine the HKm management system and the contribution of HKmto the income of the Jita Sambi HKm community in Tendambongi Village. Thisstudy conducted fromApril 5th-May 5th, 2022 in Tendambonggi Village, EndeDistrict, Ende Regency. This study targeted 29 local people, 1 person from the Ende Regency Community and Village Empowerment Service (DPMD), 1 person from the Camat of Ende District, and 2 people from the UPT KPH for Ende Regency, using purposive sampling method and Slovin formula. The analysis used both descriptive and quantitative analysis methods.Our study showed that (1) The HK management system used an intercropping pattern by planting wood,food, plantation, and horticultural crops. The dominant plants planted are coffee, chayote, and ginger.(2) HKm contributed 73.53% to the income of the community managing HKmJita Sambi, and succeeded in improving the welfare of the community while maintaining the sustainability of the forest.